1994
DOI: 10.1002/cbm.1994.4.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Mental illness as a factor in criminality: A study of prisoners and mental patients

Abstract: Data were collected on two samples of patients admitted to New York State Psychiatrie centres and two samples of inmates admitted to New York State prisons to assess the relationship between mental disorder and arrest. Differences in criminality were looked for among four groups: prisoners with no state mental hospitalisations before admission; prisoners with previous mental hospi~ talisations, patients with previous arrests, and patients with no previous arrests. Both types of patients were at lower risk of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(2 citation statements)
references
References 17 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…However, like the general population of inmates released without gradual reintegration support, offenders with mental illness are likely to be arrested again (Gendreau, Goggin, & Cullen, 1999;Harris & Koepsell, 1996;Torrey, Wolfe, & Flynn, 1992;Vose, 1990). Prior arrest is a strong predictor for future arrest and reincarceration among persons with mental illness (Cirincione, Steadman, Robbins, & Monahan, 1994).…”
Section: Mental Health Policymentioning
confidence: 99%
“…However, like the general population of inmates released without gradual reintegration support, offenders with mental illness are likely to be arrested again (Gendreau, Goggin, & Cullen, 1999;Harris & Koepsell, 1996;Torrey, Wolfe, & Flynn, 1992;Vose, 1990). Prior arrest is a strong predictor for future arrest and reincarceration among persons with mental illness (Cirincione, Steadman, Robbins, & Monahan, 1994).…”
Section: Mental Health Policymentioning
confidence: 99%
“…With few exceptions (Cirincione, Steadman, Robbins, and Monahan, in press), most have been retrospective, collecting only current charge or criminal history data. This literature yields equivocal findings: Some studies have found a relationship between mental disorder and violence (Ashford, 1989; Langevin, Ben-Aron, Wortzman, Dickey, & Handy 1987; Packard & Rosner, 1985; Roman & Gerbring, 1989; Rosner, Wiederlight, & Wieczorek, 1985; Taylor & Gunn, 1984), whereas others have not (Cirincione et al, in press; Hodgins & Cote, 1993; Phillips, Wolf, & Coons, 1988). Still others have found that it depends on the disorder (Collins & Bailey, 1990).…”
mentioning
confidence: 99%